(untitled) (Global Journal of Human-Social Science, 2020)
The present article investigated the problem of actualization of poetic ekphrasis presented in two different semiotic systems. The paper studied the correlation of generalized meaning with differing forms of expression, known as cases of isomorphism and allomorphism. The empirical material under study was provided by the contrastive analysis of the interface of one of Y. Polonskyi’s poems (1845) and N. Roerih’s original picture (1945). The contrastive pair of examples had the same titles: ’Bede, the Preacher’. The two cases were also united by identical semantics providing similar notional and emotional-aesthetic impact upon recipients, with the help of different forms of expression from poetry and painting. Both examples, in their turn, date back to the ancient legend connected with the name of the real person who lived in the seven (eight) centuries and was known as Saint Bede. The article’s aim was to reopen the enigma of identical strong emotional effect produced on recipients, at different times, with the help of two differing media forms: the poem and the picture. It actually created the evident research gap. Such cases had been studied before, but reliable explanations and technologies were not stated.